2012
DOI: 10.1039/c2mb25125f
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of the immunoproteasome in the activation of the canonical NF-κB pathway

Abstract: The discovery of NF-κB signaling pathways has greatly enhanced our understanding of inflammatory and immune responses. In the canonical NF-κB pathway, the proteasomal degradation of IκBα, an inhibitory protein of NF-κB, is widely accepted to be a key regulatory step. However, contradictory findings have been reported as to whether the immunoproteasome plays an obligatory role in the degradation of IκBα and activation of the canonical NF-κB pathway. Such results were obtained mainly using traditional gene delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Our results showing that activation of the Classical Pathway is not affected by the absence of i-proteasome subunits is consistent with a recent study that used a chemical genetic approach [36]. The authors observed no defects in TNFα-induced activation of the Classical Pathway (i.e., degradation of IκBα, nuclear translocation of p65/p50) using small molecule inhibitors that specifically target either the LMP2 or LMP7 subunits.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showing that activation of the Classical Pathway is not affected by the absence of i-proteasome subunits is consistent with a recent study that used a chemical genetic approach [36]. The authors observed no defects in TNFα-induced activation of the Classical Pathway (i.e., degradation of IκBα, nuclear translocation of p65/p50) using small molecule inhibitors that specifically target either the LMP2 or LMP7 subunits.…”
Section: Discussionsupporting
confidence: 93%
“…The fluorogenic substrate Suc-LLVY-AMC used by Mishto et al [17] is commonly used to measure the overall chymotrypsin-like activity of the proteasome. However, since this substrate can be hydrolyzed by both the immunoproteasome (β1i and β5i) and the constitutive proteasome (β5) [25], the results obtained using Suc-LLVY-AMC cannot tease out the direct contribution of the β1i genetic polymorphism. Our current results were obtained using the recently reported substrate Ac-PAL-AMC that is selectively cleaved by the β1i subunit (Figure 2) [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with small molecule inhibitors targeting LMP2 or LMP7 further supports the conception of NF-B activation being independent of proteasome composition. Inhibition of LMP2, LMP7, or even both had no influence on IB␣ degradation in cells stimulated with TNF-␣ (Jang et al, 2012). Given that neither genetic deletion nor chemical inhibition of immunoproteasome subunits affects canonical NF-B activation, the elucidation of alternative mechanisms how the immunoproteasome influences cytokine production, T helper cell differentiation, and autoimmunity requires substantial research efforts in the future.…”
Section: Discussionmentioning
confidence: 99%